Caio Fernando Abreu: em busca de Dulce e de si mesmo - Leitão, Carla Fraga (2005)
This dissertation is focused on the literary analysis surround the Caio Fernando Abreu´s novel, Onde Anadará Dulce Veiga? Um Romance B. The research has two moments: the contemporary context of the novel´s kind of writing, in Brazil, and the corpuses analysis, under the light of theories that discuss the contemporary time. The paper work asks if could Caio Fernando Abreu´s novel be showing traces that break with characteristics of the traditional novel s narrative. Its objective is a critical analysis of the narrative, checking the choices, which not only define the structural elements of the narrative but a few social and psychological aspects of the contemporary man. The theoretical argumentation is based on studies from Urlich Gumbrecht, Tânia Pellegrini, Umberto Eco, between others. Being a child of 70´s literature, Onde Anadará Dulce Veiga? Um Romance B arrives to the 90´s dragging a literary past remarkably Brazilian, incorporating non usual techniques from other arts and characterizing vividly the artistic-cultural scene in the end of the 20th century